1995
DOI: 10.1248/bpb.18.1031
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Bloodstain Age by Rapid Determinations of Oxyhemoglobin by Use of Oxygen Electrode and Total Hemoglobin.

Abstract: Bloodstain age could be estimated from the ratio of oxyhemoglobin/total hemoglobin (fractional oxyhemoglobin) in the bloodstain by this present method, if the temperature at which the bloodstain had been kept was known. The oxyhemoglobin was determined with an oxygen electrode immersed in water in which the oxygen had been depleted, and the total hemoglobin was determined by conventional colorimetry (cyanomethemoglobin method). Ages of prepared bloodstain samples (within 24 h after bleeding) were estimated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 0 publications
0
28
0
Order By: Relevance
“…1). Previous studies on Hb spectral changes with age have concentrated on the α 576 and β 541 bands [17][19], [21][24]. However, our preliminary studies indicated that neither changes to the absorption values of the α 576 and β 541 bands (or their ratios) nor the Soret band provided a sufficiently high correlation with age to be a useful TSD diagnostic (data not shown).…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…1). Previous studies on Hb spectral changes with age have concentrated on the α 576 and β 541 bands [17][19], [21][24]. However, our preliminary studies indicated that neither changes to the absorption values of the α 576 and β 541 bands (or their ratios) nor the Soret band provided a sufficiently high correlation with age to be a useful TSD diagnostic (data not shown).…”
Section: Resultsmentioning
confidence: 57%
“…The problem is that few reliable and accurate methods exist to approximate the time of deposition of these dried biological stains [16][26]. Many of the methods developed to estimate an approximate age of a bloodstain have focused on deteriorative changes to the visible spectrum of hemoglobin (Hb) over time [17][19], [21][24]. For example, one such method used the α-chain to heme ratio determined by HPLC [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Already in the 1930s Schwarzacher attempted to correlate the age of a blood stain with the blood stain's rate of inhibition of solubility in water, which begins rapid and then decreases slowly as the blood stain ages [1]. Over the last two decades, many more techniques have been explored for this forensic quest, including oxygen electrodes [2], RNA degradation [3], atomic force microscopy [4], and electron spin resonance spectroscopy [5]. Although all of these approaches confirm that the physical and chemical properties of blood stains change over time, no technique has yet shown the precision and reproducibility that is needed for age determination in forensic practice.…”
Section: Age Determination Of Blood Stainsmentioning
confidence: 99%
“…Until now, the ageing of bloodstains has been interpreted by empirical models [2], [17], [18], which hamper understanding of the oxidation decay rates and its dependency on temperature and humidity. We present reflectance spectroscopy measurements of bloodstains on cotton to determine the amount of hemoglobin derivatives in ageing bloodstains.…”
Section: Introductionmentioning
confidence: 99%